2019
DOI: 10.1021/acs.jcim.8b00730
|View full text |Cite
|
Sign up to set email alerts
|

Holo-like and Druggable Protein Conformations from Enhanced Sampling of Binding Pocket Volume and Shape

Abstract: Understanding molecular recognition of small molecules by proteins in atomistic detail is key for drug design. Molecular docking is a widely used computational method to mimic ligand−protein association in silico. However, predicting conformational changes occurring in proteins upon ligand binding is still a major challenge. Ensemble docking approaches address this issue by considering a set of different conformations of the protein obtained either experimentally or from computer simulations, e.g., molecular d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 110 publications
(292 reference statements)
1
48
0
Order By: Relevance
“…Each replica was simulated for 100 ns, leading to 400 ns of metadynamics simulations per window; coordinates were saved every 10 ps. Note that in [13] we demonstrated that EDES is not sensitive to the exact choice of the windows parameters. The height w of the Gaussian hills was set to 0.6 kcal/mol, while the widths si of the Gaussian hills were set to 0.06, 2.6, 1.7 and 3.0 respectively for RoGBS and CIP1,2,3, respectively.…”
Section: Unbiased and Enhanced-sampling Molecular Dynamics (Md) Simulmentioning
confidence: 61%
See 3 more Smart Citations
“…Each replica was simulated for 100 ns, leading to 400 ns of metadynamics simulations per window; coordinates were saved every 10 ps. Note that in [13] we demonstrated that EDES is not sensitive to the exact choice of the windows parameters. The height w of the Gaussian hills was set to 0.6 kcal/mol, while the widths si of the Gaussian hills were set to 0.06, 2.6, 1.7 and 3.0 respectively for RoGBS and CIP1,2,3, respectively.…”
Section: Unbiased and Enhanced-sampling Molecular Dynamics (Md) Simulmentioning
confidence: 61%
“…In addition, the number of protein conformations was lowered to 200 to cope with the time constraints of the challenge, also considering that for each compound, 10 ligand conformations were employed in ensemble-docking runs. Protein conformations were extracted by means of a multi-step cluster analysis as described in [13], with the additional requirement to extract at least 10 cluster representatives from each of the 10 slices in which the RoGBS distributions were binned, so as to include a certain number of structures also from poorly sampled regions. The multi-step cluster analysis was applied separately to MDapo and EDES3w, extracting 500 clusters from each trajectory.…”
Section: Dockingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, proteins are dynamic and possess an inherent flexibility 17 which alters the shape and properties of their binding pockets. [18][19][20] Therefore, it is valuable to explore the different conformations of a binding pocket by molecular simulation and the corresponding variations in druggability. Some methods that combine pocket druggability prediction and molecular dynamics simulation have been developed, such as MDpocket 21 and JEDI.…”
Section: Introductionmentioning
confidence: 99%